INFLUENCE ANALYSIS OF FUNDAMENTAL AND SYSTEMATIC RISK FACTORS OF SHARE RPICE ON THE COMPANY TRADE IN INDONESIA STOCK EXCHANGE (IDX) - Herry Sussanto; Dika Nurliana (Universitas Gunadarma, 2009)
Trades and industries play an important role in economic development. Firms operating in these sectors are required to increase their performance and to improve their competitiveness in order to maintain their existence. This study is aimed at analyzing effect of fundamental factors and systematic risks on stock price of firms operating in trade sector. Thirty firms were selected from 37 firms listed at the Indonesia Stock Exchange (IDX) using purposive sampling method (i.e., firms that provides financial statements from 2005-2007). Data were analyzed using multiple linear regression analysis. The study results showed that all fundamental factors (i.e., return on asset, return on equity, book value, dividend ratio, debt to equity ratio, and expected rate of return) and systematic risk (i.e., beta) simultaneously affect stock price. Systematic risk was found to partially affect stock price. Meanwhile, fundamental factors which partially have significant effect on stock price include book value and expected rate of return.Key words: fundamental factors; systematic risk; stock price.1